Unemployment in the Warmińsko-Mazurskie and Wielkopolskie Voivodeships – a Comparative Analysis - Koziej, Julia; Kutryb, Kinga (Olsztyn Economic Journal, 2024)
Unemployment is a phenomenon that has significant consequences for society as well as for the economic development of a country, as it is a problem that manifests in both economic and social dimensions. Notably, there are significant differences in the extent of this phenomenon based on age, gender, place of residence, education, and spatial distribution. The lowest unemployment rate in Poland is observed in the Wielkopolskie voivodeship, while one of the highest is found in the Warmińsko-Mazurskie voivodeship. These differences arise from the distinct demographic, production, and infrastructural structures of these regions. However, the scale of these differences changes over time and may vary across different age groups or gender divisions. In light of the above, the aim of this study was to conduct a comparative analysis of the total unemployment and unemployment by age and gender in the Warmińsko-Mazurskie and Wielkopolskie voivodeships. The analysis covers the period from 2012 to 2022, based on data from the Central Statistical Office. The conducted research shows that the unemployment rate in the years 2012-2022 (except for 2020) decreased in both voivodeships. In 2022, the unemployment rate in the Wielkopolskie voivodeship was the lowest in the country, while the Warmińsko-Mazurskie voivodeship was in the penultimate position in this respect, right after the Podkarpackie voivodeship. In all the years analyzed, in both regions, a higher share of unemployed people in the number of working-age population was recorded in the case of women, although a downward trend was also noted in this respect. The conducted analyses also showed that throughout the entire period under review, the lowest unemployment in both analyzed voivodeships occurred among the age group of 35-44 years. Interestingly, in 2022, in the Wielkopolskie voivodeship, the highest unemployment occurred among people aged 18-24, while in the Warmińsko-Mazurskie voivodeship in the age group of 25-34 years.